Associations between participant characteristics, digital intervention engagement and recovery outcomes for participants accessing 'Breaking Free Online' at 'Change Grow Live'. (3rd September 2021) - Elison-Davies, Sarah; Hayhurst, Karen; Jones, Andrew; Welch, Zoe; Davies, Glyn; Ward, Jonathan
ABSTRACT: Background: Digital interventions can be tailored to the individual and allow automated collection of data. Computer-assisted therapy program 'Breaking Free Online' (BFO) is delivered within 'Change Grow Live' (CGL) services to support people in recovery from substance misuse. This paper reports baseline data from 5792 participants engaging with BFO at CGL, and post-treatment outcomes from 1489 (26%), and describes how baseline characteristics and BFO engagement were associated with outcomes. Methods: Participants completed a baseline assessment, engaged with BFO and completed a post-treatment assessment. Wilcoxon tests examined changes from baseline to post-treatment and linear regression examined associations between baseline service user characteristics, BFO engagement and outcomes. Results: Participants who did not provide post-treatment data had more severe mental health and biopsychosocial impairment at baseline. Outcomes were associated with baseline characteristics including substance use and dependence, biopsychosocial impairment, age and BFO engagement. Outcomes were significantly positively associated with the number of techniques in BFO completed, indicating a 'dose-response'. Conclusions: Findings indicate positive outcomes for CGL service users who engaged with BFO through to post-treatment outcomes assessment stage. Stratifying BFO to those most likely to engage may improve treatment outcomes. Some groups may benefit from receiving BFO as 'computer-assisted therapy' with Practitioner support.